Effects of strategic helminthosis control on age at first lambing and lambing interval of communally grazed Menz ewes in Ethiopia - Aragaw, K.; Teferi, M.; Haile, Aynalem; Tibbo, Markos (Elsevier, 2011)
A three-year longitudinal study was conducted to evaluate effects of strategic anthelmintic treatment regimes on age at first lambing (AFL), weight at first lambing (WFL) and lambing interval (LI) of 356 communally grazed ewes and 675 lambs owned by 10 smallholder farmers in the central highlands of Ethiopia. The ewes were stratified by weight and randomly allocated to three treatment groups as untreated control (TG1), twice-dosed per year (TG2) for both nematodes and trematodes in mid-January and mid-June and four-time-dosed per year (TG3) in June for nematodes, in August–September for nematodes and adult Fasciola, in November–December and January–February for immature flukes. The fixed effect of anthelmintic treatments, parity, season and year of lambing on AFL and LI was evaluated. Mean ± standard error (SE) of lambing interval was 292 ± 3 days. Both anthelmintic treatments (TG2 and TG3) shortened (P < 0.01) LI by about 23 days compared to non-treated ewes (TG1). Season and year of lambing had a significant (P < 0.001) effect on LI. Mean ± SE of AFL and WFL was 598 ± 10 days and 17.2 ± 1.37 kg, respectively. Anthelmintic treatments and parity of dam of the ewe lamb did not affect AFL (P > 0.05). Birth and lambing seasons of the ewe lamb had significant (P < 0.05) effect on AFL. On the other hand, lambing season of the ewe had significant (P < 0.05) effect on WFL. Ewe lambs born in the long rains lambed more than 50 days earlier than the ewe lambs born in short rainy and dry seasons. Lambing occurred year-round with two peaks in August–September and December–January, each 5 months after the two rainy seasons. Anthelmintic treatment at the beginning of the two rainy seasons should improve reproductive performance of Menz ewe lambs in similar agro-ecology in the central highlands of Ethiopia.